Optimal Grid-Connected PV System for a Campus Microgrid - Mohammed Reyasudin Basir Khan; Jagadeesh Pasupuleti; Jabbar Al-Fattah; Mehrdad Tahmasebi (Indonesian Journal of Electrical Engineering and Computer Science, 2018)
This paper discusses on the implementation of a grid-connected PV system for university campus in Malaysia. The primary goal of this study is to develop a grid-connected microgrid comprises of Photovoltaic (PV) and a battery storage system to meet the campus load demand and minimize grid dependency. The microgrid modeled and simulated in Hybrid Optimization Model for Electrical Renewable (HOMER) software. Actual load profile and renewable resources were used as an input parameter for the hybrid system. The campus selected is Universiti Kuala Lumpur, British Malaysian Institute as it represents typical load profile for a small campus. Therefore, the results can be used to represent hybrid system development for other small campuses in Malaysia as well. Firstly, optimal sizing of renewable energy (RE) were simulated with respect to total Net Present Cost (NPC) and Cost of Energy (COE). Then, sensitivity analysis conducted to determine the system performance based on changes of load growth, and renewable resources. The results demonstrate optimal HRES combinations for the campus microgrid comprises of 50 kWp of PV generations with 50 kW inverter. However, inclusion of 576 kWh battery storage system will increase the NPC but has higher RE penetration.